Preparation and application of a super-hydrophilic anti-protein fouling material
By combining polydopamine with a vertically ordered mesoporous silica film on the electrode and depositing gold nanoparticles in the pores, the problem of poor stability of VMSF is solved, and high sensitivity detection of acetaminophen and anti-fouling of electrodes is achieved. Performance, detection range is 10-200μM.
Patent Information
- Application Number
- CN202210929282.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-03
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-08-03
AI Technical Summary
The stability of the vertically ordered mesoporous silica film in the existing electrodes is poor, resulting in failure in preparation and poor detection performance, especially when the binding force is weak when combined with VMSF on the glass carbon electrode, affecting the detection sensitivity.
Polydopamine is used to combine with vertically ordered mesoporous silica film, and gold nanoparticles are deposited in the pores to form a polydopamine film with amide and gold nanoparticles-vertical ordered mesoporous silica film composite Membrane-modified electrodes enhance the stability and detection performance of VMSF.
Improves the mechanical stability of VMSF on the electrode surface and the stability of gold signal, realizes high sensitivity detection of acetaminophen, with a detection range of 10-200μM, and has super hydrophilic properties and anti-protein adsorption ability, enhancing the electrode Anti-fouling performance.
Smart Images

Figure CN115308283B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical sensor electrode materials, and in particular to the preparation and application of a super-hydrophilic anti-protein fouling material. Background Art
[0002] Acetaminophen (APAP) is an acetanilide drug, has antipyretic, analgesic effect, is widely used in Chinese and Western medicine and its preparation, can be used for cold fever, arthralgia, neuralgia and migraine, cancer pain, toothache and postoperative analgesia, can also be used for patients (varicella, hemophilia and other hemorrhagic diseases etc.) who are allergic to aspirin, are intolerant or are not suitable for using aspirin. However, acetaminophen has certain toxic and side effects, and short-term use generally does not cause gastrointestinal bleeding, but excessive taking will cause symptoms such as nausea, vomiting, anorexia, sweating, abdominal pain, and cause liver damage, and can also cause coma or even death when serious. Therefore, the detection method of acetaminophen is of great significance in terms of physiological function and clinical application.
[0003] Electrochemically modified electrodes have become the most active frontier field of electrochemistry and electroanalytical chemistry since their development in the 1970s. It is a method of modifying the surface of a conductor or semiconductor electrode by chemical or physicochemical methods to form a thin film with the desired function, thereby giving the electrode a specific physicochemical structure. It can be applied to electrochemical sensors, capillary electrophoresis detectors, liquid chromatography detectors, flow injection detectors, ion chromatography detectors, etc.
[0004] Vertically ordered mesoporous silica films (VMSF) are excellent anti-interference and anti-fouling materials, and have been widely used in separation, sensing and other fields. In the field of sensing, the uniformly distributed mesoporous channels are arranged vertically and orderly on the substrate material, which gives it a certain size selection effect. Combined with ultra-thin thickness and high pore density, it can further improve its anti-interference and ability to prevent nonspecific adsorption of substances such as proteins. Usually, electrochemically assisted self-assembly can be used to prepare VMSF on different electrodes such as glassy carbon electrodes, ITO electrodes, and gold electrodes. However, when preparing VMSF on glassy carbon electrodes, the weak binding force between the two often causes VMSF to fall off, resulting in preparation failure. Considering that VMSF is a silicon-containing material, a hydroxyl-containing adhesive can be introduced on the surface of the glassy carbon electrode by using the covalent bonding between silicon atoms and hydroxyl groups, so that VMSF can be stably present on the electrode. Existing adhesives that improve the stability of VMSF include aminopropyltriethoxysilane, reduced graphene oxide and other materials. In order to further strengthen the bonding force between the glassy carbon electrode and VMSF, it is very necessary to continue exploring suitable adhesives to improve the stability of VMSF and further improve the detection performance of the sensing platform.
[0005] Polydopamine (PDA) is a multifunctional agent inspired by mussels. It is considered a strong adhesive because it exhibits remarkable adhesive properties on almost any material surface. So far, the method of using polydopamine as an adhesive to improve the stability of the sensing platform has been widely used, and the excellent biocompatibility and hydrophilicity of polydopamine broaden the scope of use of the sensing platform while giving it excellent sensing performance. Therefore, if VMSF and PDA can be combined to modify the electrode, it will be beneficial to improve the stability of VMSF and further improve the detection sensitivity of acetaminophen. Summary of the invention
[0006] The invention prepares an electrode modification material by combining polydopamine and a vertical ordered mesoporous silica film, so as to solve the problem of poor stability of the vertical ordered mesoporous silica film in the existing electrode.
[0007] In order to achieve the above object, the technical solution of the present invention is as follows:
[0008] A method for preparing an amination-modified polydopamine film-vertically ordered mesoporous silica film composite film modified electrode loaded with gold nanoparticles, the preparation method comprising the following steps:
[0009] Step 1: preparing a polydopamine film on the electrode surface to obtain a polydopamine film-modified electrode;
[0010] Step 2: preparing a vertical ordered mesoporous silica film on the surface of the electrode modified with the polydopamine film in step 1, to obtain an electrode modified with the polydopamine film and the vertical ordered mesoporous silica film;
[0011] Step 3: The polydopamine membrane and vertical ordered mesoporous silica membrane modified electrode of step 2 are amino-modified, and then gold nanoparticles are deposited in the pores of the vertical ordered mesoporous silica membrane to obtain an amino-modified polydopamine membrane-vertical ordered mesoporous silica membrane composite membrane modified electrode loaded with gold nanoparticles.
[0012] In some embodiments, the step 1 specifically comprises: immersing the polished and cleaned electrode in a solution having a concentration of 1.0 to 4.0 mg·mL -1 The polydopamine solution is subjected to self-polymerization reaction at room temperature for 1 to 4 hours to obtain a polydopamine film.
[0013] Furthermore, the electrode was first polished with 0.3 and 0.05 μm alumina slurries, and then ultrasonically cleaned with ethanol and water for 3 minutes.
[0014] In some embodiments, the concentration of the dopamine solution is 2.0 mg·mL -1 , the self-polymerization time is 3h.
[0015] In some embodiments, step 2 specifically includes the following steps:
[0016] Step 3.1: Prepare a precursor solution, dissolve tetraethoxysilane and hexadecyltrimethylammonium bromide in a mixed solution of 0.1-0.3M NaNO3 solution and an equal amount of ethanol, adjust the pH to 1.0-4.0, and stir at room temperature for pre-hydrolysis before use;
[0017] Step 3.2: The electrode modified with the polydopamine film is used as the working electrode and immersed in the precursor solution. A constant potential of -5 to -1 V is applied for 5 to 15 seconds to grow a vertical ordered mesoporous silica film. The electrode is taken out, rinsed and dried, and then immersed in a 0.1M to 0.3M HCl-ethanol solution to remove the surfactant micelles to obtain an electrode modified with a polydopamine film and a vertical ordered mesoporous silica film.
[0018] In some of the embodiments, in step 3.1, the concentration of the NaNO3 solution is 0.1 M, and the pH of the mixed solution is 3.0.
[0019] In some embodiments, the voltage of the constant potential is -2.2 V, and the concentration of the HCl-ethanol solution is 0.1 M.
[0020] In some of the embodiments, the step 3 specifically includes: first immersing the polydopamine membrane-vertical ordered mesoporous silica membrane composite membrane modified electrode prepared in step 2 in a 5-15% (v / v) 3-aminopropyltriethoxysilane solution for amination, and then immersing it in a 0.2-1.0% HAuCl4 aqueous solution after washing, and applying a voltage of -0.8 to -0.1V for 1 to 6s to obtain an amination- and gold nanoparticle-loaded polydopamine membrane-vertical ordered mesoporous silica membrane composite membrane modified electrode.
[0021] In some of the embodiments, the volume percentage of the 3-aminopropyltriethoxysilane solution is 10% (v / v), the mass percentage of the HAuCl4 is 0.5%, and a voltage of -0.5 V is applied for 3 s.
[0022] In some of the embodiments, the method for preparing an electrode modification material is used to prepare an aminated polydopamine film-vertically ordered mesoporous silica film composite film modified electrode loaded with gold nanoparticles.
[0023] In some of the embodiments, the amino-modified and gold nanoparticle-loaded polydopamine film-vertically ordered mesoporous silica film composite film modified electrode is used in the detection of acetaminophen.
[0024] The beneficial effects of the present invention are as follows:
[0025] The invention adopts a dopamine self-polymerization method to prepare a polydopamine film on the electrode surface, then grows a vertical ordered mesoporous silica film (VMSF) on the electrode surface modified by the polydopamine film, and then electrochemically deposits gold nanoparticles in the pores of the vertical ordered mesoporous silica film after the polydopamine film and the electrode modified by the vertical ordered mesoporous silica film are aminated, thereby obtaining an aminated polydopamine film-vertical ordered mesoporous silica film composite film modified electrode loaded with gold nanoparticles. Polydopamine contains abundant catechol groups, and the hydroxyl group can be covalently bonded with VMSF, thereby improving the mechanical stability of VMSF on the electrode surface, and also improving the signal stability of the gold nanoparticles. The stable gold signal can construct an antifouling ratio electrochemical sensing platform, further realizing the highly sensitive detection of electroactive small molecules, especially acetaminophen, with a detection range of 10-200 μM. In addition, the aminated VMSF has super hydrophilicity in combination with polydopamine, thereby being able to resist the nonspecific adsorption of substances such as proteins, and having certain anti-protein adhesion and anti-bacterial adhesion properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the implementation mode will be briefly introduced below. Obviously, the drawings described below are only some implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is a flow chart for the preparation of modified electrode materials.
[0028] Figure 2 These are the actual shots of contact angle tests of different modified electrodes and the signal change curves of gold. In the figure: A is the actual shot of contact angle of electrode PDA / GCE, electrode VMSF / GCE, electrode NH2-VMSF / GCE, electrode NH2-VMSF / PDA / GCE, and electrode AuNP@NH2-VMSF / PDA / GCE; B is the CV test graph of electrode GCE, electrode AuNP@VMSF / GCE, electrode Au NP@NH2-VMSF / GCE, and electrode AuNP@NH2-VMSF / PDA / GCE; C is the DPV test graph of electrode GCE, electrode AuNP@VMSF / GCE, electrode AuNP@NH2-VMSF / GCE, and electrode AuNP@NH2-VMSF / PDA / GCE.
[0029] Figure 3 These are actual pictures and signal change diagrams of different modified electrodes. In the figure: A is an actual picture of electrodes SM@VMSF / GCE, VMSF / GCE, SM@VMSF / PDA / GCE, VMSF / PDA / GCE; B is a CV test signal change diagram of electrodes AuNP@VMSF / GCE, AuNP@NH2-VMSF / GCE, AuNP@NH2-VMSF / PDA / GCE after 10 cycles; C is a gold signal change diagram of electrodes AuNP@VMSF / GCE, AuNP@NH2-VMSF / GCE, AuNP@NH2-VMSF / PDA / GCE after 12 hours.
[0030] Figure 4 This is a graph of signal changes of different electrodes under the interference of 0.1 mg / ml, 0.5 mg / ml, and 1 mg / ml bovine serum albumin. In the graph: A is the electrode AuNP@VMSF / GCE, B is the electrode AuNP@NH2-VMSF / GCE, and C is the electrode AuNP@NH2-VMSF / PDA / GC.
[0031] Figure 5This is a graph showing the change in gold signal after APAP is added to the modified electrode AuNP@NH2-VMSF / PDA / GCE. In the graph: A is the CV test of the electrode AuNP@NH2-VMSF / PDA / GCE before and after APAP is added; B is the DPV test of the electrode AuNP@NH2-VMSF / PDA / GCE before and after APAP is added; C is the DPV test of the electrode AuNP@NH2-VMSF / PDA / GCE after different concentrations of APAP are added; and D is a linear fitting graph. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. The experimental methods in the following examples are conventional unless otherwise specified.
[0033] Example 1: Preparation method of an amination-modified and gold nanoparticle-loaded polydopamine film-vertically ordered mesoporous silica film composite film modified electrode
[0034] according to Figure 1 The preparation process of the electrode modification material specifically comprises the following steps:
[0035] 1. Polish the glassy carbon electrode (GCE) on a polishing cloth with 0.3 μm and 0.05 μm alumina slurries, respectively, and then ultrasonically clean it in anhydrous ethanol and ultrapure water for 3 min.
[0036] 2. Immerse the glassy carbon electrode cleaned in step 1 into 2.0 mg mL -1 The polydopamine (PDA) solution (prepared by dissolving dopamine in 10 mM Tris-HCl buffer, pH = 8.5) was self-polymerized at room temperature for 3 h to obtain a polydopamine film-modified glassy carbon electrode, denoted as PDA / GCE.
[0037] 3. A vertical ordered mesoporous silica film (VMSF) was prepared on PDA / GCE by an electrochemically assisted self-assembly method, specifically comprising: 1) dissolving 2.833 g of tetraethoxysilane and 1.585 g of hexadecyltrimethylammonium bromide in a mixed solution of 20 mL of 0.1 M NaNO3 solution and an equal amount of anhydrous ethanol to obtain a precursor solution; 2) adjusting the pH of the precursor solution to 3.0 with HCl, stirring and pre-hydrolyzing at room temperature for 2.5 h, and then immersing the PDA / GCE prepared in step 2 as a working electrode in the precursor solution, and applying - The vertical ordered mesoporous silica film (VMSF) was grown at a constant potential of 2.2 V for 10 s; 3) after the growth of VMSF, the working electrode was quickly taken out from the precursor solution, rinsed with a large amount of ultrapure water, and then dried and cured in an oven at 80 ° C overnight; 4) in order to remove the surfactant micelles (SM) in the VMSF nanochannel, the working electrode was immersed in 0.1 M HCl-ethanol solution and stirred for 5 min, and finally a glassy carbon electrode modified with a polydopamine membrane-vertical ordered mesoporous silica membrane composite film was obtained, which was recorded as VMSF / PDA / GCE.
[0038] 4. The glassy carbon electrode VMSF / PDA / GCE prepared in step 3 was immersed in an ethanol solution containing 10% (v / v) 3-aminopropyltriethoxysilane (APTES) overnight for amination, washed with anhydrous ethanol and ultrapure water in turn, and then immersed in an aqueous solution of 0.5% HAuCl4, and a voltage of -0.5 V was applied for 3s to obtain a glassy carbon electrode modified with a polydopamine film-vertically ordered mesoporous silica film composite film loaded with gold nanoparticles, which was recorded as AuNP@NH2-VMSF / PDA / GCE.
[0039] Comparative Example 1: Preparation method of an electrode modification material
[0040] The preparation method is the same as steps 1-2 in Example 1 to obtain a glassy carbon electrode PDA / GCE modified only with polydopamine.
[0041] Comparative Example 2: Preparation method of an electrode modification material
[0042] After the glassy carbon electrode is polished and cleaned according to step 1 in Example 1, a vertical ordered mesoporous silica film (VMSF) is prepared on the surface of the glassy carbon electrode by the electrochemically assisted self-assembly method in step 3 in Example 1 to obtain a glassy carbon electrode VMSF / GCE modified only with the vertical ordered mesoporous silica film.
[0043] Comparative Example 3: Preparation method of an electrode modification material
[0044] The electrode VMSF / GCE prepared in comparative example 2 was immersed in an ethanol solution containing 10% (v / v) 3-aminopropyltriethoxysilane (APTES) overnight for amination to obtain a glassy carbon electrode NH2-VMSF / GCE modified with only the amination vertical ordered mesoporous silica film.
[0045] Comparative Example 4: Preparation method of an electrode modification material
[0046] The preparation method is the same as that in Example 1, except that after amination, the gold nanoparticles are not loaded by immersion in a 0.5% HAuCl4 aqueous solution, thereby obtaining an amination polydopamine film-vertical ordered mesoporous silica film composite film modified glassy carbon electrode NH2-VMSF / PDA / GCE.
[0047] Comparative Example 5: Preparation method of an electrode modification material
[0048] The electrode VMSF / GCE prepared in Comparative Example 2 was washed with ultrapure water and then immersed in a 0.5% HAuCl4 aqueous solution, and a voltage of -0.5 V was applied for 3 seconds to obtain a glassy carbon electrode AuNP@VMSF / GCE modified with a vertical ordered mesoporous silica film loaded with gold nanoparticles.
[0049] Comparative Example 6: Preparation method of an electrode modification material
[0050] The electrode NH2-VMSF / GCE prepared in comparative example 3 was washed with anhydrous ethanol and ultrapure water and then immersed in an aqueous solution of 0.5% HAuCl4, and a voltage of -0.5 V was applied for 3 seconds to obtain a glassy carbon electrode AuNP@NH2-VMSF / GCE modified with a vertical ordered mesoporous silica film that was amino-loaded with gold nanoparticles.
[0051] Experimental Example 1: Analysis of the electrochemical properties of different electrode modification materials
[0052] 1. The hydrophilic wetting angle is small, and water will spread out; the hydrophobic wetting angle is large, and water forms round drops. A contact angle meter was used to analyze the effects of different electrode modification materials prepared in Example 1 and Comparative Examples 1-4 on electrode wettability.
[0053] Experimental results:
[0054] like Figure 2As shown in A, PDA / GCE is a glassy carbon electrode modified with only polydopamine, VMSF / GCE is a glassy carbon electrode modified with only vertical ordered mesoporous silica film, NH2-VMSF / GCE is a glassy carbon electrode modified with only aminated vertical ordered mesoporous silica film, NH2-VMSF / PDA / GCE is an aminated vertical ordered mesoporous silica film and a glassy carbon electrode modified with polydopamine, and AuNP@NH2-VMSF / PDA / GCE is an aminated vertical ordered mesoporous silica film loaded with gold nanoparticles and a glassy carbon electrode modified with polydopamine prepared in Example 1. The glassy carbon electrodes NH2-VMSF / PDA / GCE and AuNP@NH2-VMSF / PDA / GCE modified with polydopamine (PDA) and vertical ordered mesoporous silica film (VMSF) have certain hydrophilicity. Polydopamine as a binder not only improves the stability of VMSF, but also makes the glassy carbon electrode modified with VMSF more hydrophilic than the electrode modified with a single component. It can be seen from AuNP@NH2-VMSF / PDA / GCE that after electrochemical deposition of gold nanoparticles in the pores of aminated VMSF, the glassy carbon electrode exhibits superhydrophilicity when modified, and its water contact angle is below 5°.
[0055] 2. Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were used in 0.3M PBS solution (pH=7) using a CHI650E electrochemical workstation (source: Shanghai Chenhua Instrument Co., Ltd.) to test the gold signal changes of ordinary glassy carbon electrodes or different electrode modification materials prepared in Comparative Examples 1-4. The CV test potential range was set to 0-1.1V, the scan rate was 100mV / s, and the number of scan segments was 2; the DPV test scan range was 1.1V-0V, the amplitude was 0.05V, the pulse width was 0.05s, and the sampling period was 0.0167s.
[0056] Experimental results:
[0057] like Figure 2As shown in B and 2C, GCE is an ordinary glassy carbon electrode, AuNP@VMSF / GCE is a glassy carbon electrode modified with a vertical ordered mesoporous silica film loaded with gold nanoparticles, AuNP@NH2-VMSF / GCE is a glassy carbon electrode modified with a vertical ordered mesoporous silica film loaded with gold nanoparticles after being aminated, and AuNP@NH2-VMSF / PDA / GCE is a glassy carbon electrode modified with a vertical ordered mesoporous silica film loaded with gold nanoparticles and polydopamine prepared in Example 1. The currents of electrode AuNP@NH2-VMSF / GCE and electrode AuNP@NH2-VMSF / PDA / GCE are higher than those of electrode GCE and electrode AuNP@VMSF / GCE. In addition, electrode AuNP@NH2-VMSF / GCE and electrode AuNP@NH2-VMSF / PDA / GCE are both amino-modified, indicating that the amino-modified VMSF can load more gold nanoparticles. The gold signal decreases after using polydopamine, which further proves the successful synthesis of polydopamine on the modified electrode.
[0058] 3. Analyze the mechanical stability of the glassy carbon electrode AuNP@NH2-VMSF / GCE or AuNP@NH2-VMSF / PDA / GCE during the preparation process. The specific operation includes: immersing the glassy carbon electrode VMSF / GCE or VMSF / PDA / GCE in a 0.1M HCl-ethanol solution and stirring for 5 minutes to remove the surfactant micelles (SM), and then observing the shedding of VMSF on the glassy carbon electrode with the naked eye, and then setting the glassy carbon electrode SM@VMSF / GCE or SM@VMSF / PDA / GCE without removing the surfactant micelles (SM) as the control group.
[0059] Experimental results:
[0060] like Figure 3 As shown in A, when polydopamine is not used as a binder, VMSF is easily detached from the electrode surface after the surfactant micelles are removed. However, when polydopamine is used as a binder, VMSF can still stably exist on the electrode surface after the surfactant micelles are removed.
[0061] 4. In 0.3M phosphate buffer (pH=7), the electrode modification materials prepared in Example 1, Comparative Example 5, and Comparative Example 6 were subjected to 10 cycles of CV test respectively by CHI650E electrochemical workstation (source: Shanghai Chenhua Instrument Co., Ltd.), and then the gold signal change of the electrode modification materials after being placed in the phosphate buffer for 12 hours was tested by CV to verify the stability of the signal. The CV test potential range was set to 0-1.1V, the scan rate was 100mV / s, and the number of scan segments was 20.
[0062] Experimental results:
[0063] like Figure 3 As shown in B, after repeated CV scans, the CV curve of the electrode using polydopamine as a linker has almost no change, while the peak current of the CV curve of the electrode without polydopamine has decreased. Figure 3 As shown in Figure C, after 12 hours of placement, the gold signal of AuNP@NH2-VMSF / PDA / GCE has almost no change, while the gold signal of AuNP@NH2-VMSF / GCE has a certain fluctuation and decrease.
[0064] 5. Add 0.1mg / ml, 0.5mg / ml, and 1mg / ml bovine serum albumin (BSA) as interfering protein to 0.3M phosphate buffer (pH=7), and then use CHI650E electrochemical workstation (from Shanghai Chenhua Instrument Co., Ltd.) to measure the antifouling performance of the electrode by using DPV test electrode gold signal changes. Set the DPV test scanning range to 1.1V-0V, amplitude to 0.05V, pulse width to 0.05s, and sampling period to 0.0167s.
[0065] Experimental results:
[0066] Figure 4 A is a vertical ordered mesoporous silica film modified with gold nanoparticles AuNP@VMSF / GCE. Figure 4 B is a vertical ordered mesoporous silica film modified with amino and gold nanoparticles, AuNP@NH2-VMSF / GCE. Figure 4 C is an amino-modified vertically ordered mesoporous silica film loaded with gold nanoparticles and a polydopamine-modified glassy carbon electrode. Figure 4 A and Figure 4 As shown in Figure B, when polydopamine is not used as a binder, the higher the concentration of bovine serum albumin, the lower the gold signal, proving that the interference of bovine serum albumin in the electrolyte solution causes a significant decrease in the gold signal (27.4%, 11.4%). Figure 4 As shown in C, after using polydopamine as a binder, the gold signal of the electrode has almost no change (1.6%), proving that the polydopamine-modified electrode has excellent hydrophilicity, thereby being able to effectively improve the antifouling performance of the electrode.
[0067] 6. Analysis of the electrochemical behavior of acetaminophen on the glassy carbon electrode AuNP@NH2-VMSF / PDA / GCE
[0068] The electrode AuNP@NH2-VMSF / PDA / GCE was tested by CV and DPV using a CHI650E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.) before and after adding acetaminophen (APAP) at 250 μM, and then DPV was tested at APAP concentrations of 10, 38.5, 56.6, 74.1, 90.9, 130.4, 166.7, and 200 μM. The vertical ordered mesoporous silica film loaded with gold nanoparticles after amino modification and the glassy carbon electrode AuNP@NH2-VMSF / PDA / GCE modified with polydopamine were used as working electrodes, platinum wire electrodes were used as counter electrodes, saturated calomel electrodes (SCE) were used as reference electrodes, and phosphate buffer was used as electrolytes. Set the CV test potential interval to 0-1.1 V, the scan rate to 100 mV / s, and the number of scan segments to 2; the DPV test scan range to 1.1 V-0 V, the amplitude to 0.05 V, the pulse width to 0.05 s, and the sampling period to 0.0167 s.
[0069] Experimental results:
[0070] The modified electrode obtained a pair of gold redox peaks in phosphate buffer, where the gold reduction peak was around 0.5V. After the addition of APAP, a pair of new redox peaks belonging to APAP were obtained, with a reduction potential of around 0.3V, which can be clearly distinguished from the gold reduction peak. Figure 5 As shown in A, after adding 25 μM APAP to the electrolyte solution, in addition to the redox peak of gold, an additional redox peak of APAP was obtained, and the redox peak of gold did not change with the addition of APAP. Figure 5 As shown in Figure B, when DPV testing was performed, a new reduction peak appeared in the DPV curve of the electrode with APAP added, while the reduction peak of gold did not change. Figure 5 As shown in C, as the APAP concentration increases, the peak current of APAP in the DPV curve of the electrode also increases. Figure 5 As shown in D, a linear fit was performed between the ratio of the APAP peak current to the gold peak current and the APAP concentration, and the fitting equation was obtained as IAPAP / IAu=0.31396+0.00227CAPAP(R 2 =0.9977), and the linear range was 10-200 μM.
[0071] In summary, the polydopamine film-vertical ordered mesoporous silica film composite film prepared by the present invention and loaded with gold nanoparticles is used to modify the glassy carbon electrode. Compared with the existing electrode modification materials, the use of polydopamine as an adhesive can not only improve the mechanical stability of the vertical ordered mesoporous silica film (VMSF) and the signal stability of the gold nanoparticles, but also show superhydrophilicity in combination with VMSF. Even under the interference of bovine serum albumin, the gold signal of the electrode has almost no change. Its excellent hydrophilicity makes the composite film have certain anti-protein fouling and anti-bacterial adhesion properties. In addition, the stable gold signal can also achieve high-sensitivity detection of acetaminophen, with a detection range of 10-200μM.
[0072] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A method for preparing an aminated polydopamine film-vertically ordered mesoporous silica film composite film modified electrode loaded with gold nanoparticles, characterized in that: The preparation method comprises the following steps: Step 1: Prepare a polydopamine film on the electrode surface to obtain a polydopamine film-modified electrode; specifically, immerse the polished and cleaned electrode in a solution having a concentration of 1.0 to 4.0 mg mL -1 In a dopamine solution, self-polymerize at room temperature for 1 to 4 hours to obtain a polydopamine film; Step 2: preparing a vertical ordered mesoporous silica film on the surface of the polydopamine film-modified electrode in step 1 to obtain a polydopamine film and a vertical ordered mesoporous silica film-modified electrode; specifically comprising the following steps: Step 2.1: Prepare a precursor solution: dissolve tetraethoxysilane and hexadecyltrimethylammonium bromide in a mixed solution of 0.1-0.3M NaNO3 solution and an equal amount of ethanol, adjust the pH to 1.0-4.0, and stir at room temperature for pre-hydrolysis before use; Step 2.2: The electrode modified with the polydopamine film is used as the working electrode and immersed in the precursor solution, and a constant potential of -5 to -1 V is applied for 5 to 15 seconds to grow a vertical ordered mesoporous silica film. The electrode is taken out, rinsed and dried, and then immersed in a 0.1M to 0.3M HCl-ethanol solution to remove the surfactant micelles, thereby obtaining an electrode modified with a polydopamine film and a vertical ordered mesoporous silica film; Step 3: amination the polydopamine membrane and vertical ordered mesoporous silica membrane modified electrode of step 2, and then depositing gold nanoparticles in the pores of the vertical ordered mesoporous silica membrane to obtain an amination- and gold nanoparticle-loaded polydopamine membrane-vertical ordered mesoporous silica membrane composite membrane modified electrode; specifically: First, immerse the polydopamine membrane-vertical ordered mesoporous silica membrane composite membrane modified electrode prepared in step 2 in a 5-15% by volume 3-aminopropyltriethoxysilane solution for amination, and then immerse it in a 0.2-1.0% HAuCl4 aqueous solution after washing, and apply a voltage of -0.8 to -0.1V for 1 to 6s to obtain an amination- and gold nanoparticle-loaded polydopamine membrane-vertical ordered mesoporous silica membrane composite membrane modified electrode.
2. The method for preparing an aminated polydopamine film-vertically ordered mesoporous silica film composite film modified electrode loaded with gold nanoparticles according to claim 1, characterized in that: The concentration of the dopamine solution is 2.0 mg·mL -1 The self-polymerization reaction time is 3h.
3. The method for preparing an aminated and gold nanoparticle-loaded polydopamine film-vertically ordered mesoporous silica film composite film modified electrode according to claim 1, characterized in that: In step 2.1, the concentration of the NaNO3 solution is 0.1 M, and the pH of the mixed solution is 3.
0.
4. The method for preparing an aminated and gold nanoparticle-loaded polydopamine film-vertically ordered mesoporous silica film composite film modified electrode according to claim 1, characterized in that: In step 2.2, the voltage of the constant potential is -2.2 V, and the concentration of the HCl-ethanol solution is 0.1 M.
5. The method for preparing an aminated polydopamine film-vertically ordered mesoporous silica film composite film modified electrode loaded with gold nanoparticles according to claim 1, characterized in that: The volume percentage of the 3-aminopropyltriethoxysilane solution is 10%, the mass percentage of the HAuCl4 is 0.5%, and a voltage of -0.5 V is applied for 3 seconds.
6. A polydopamine film-vertically ordered mesoporous silica film composite film modified electrode prepared by the preparation method according to any one of claims 1 to 5 and loaded with gold nanoparticles.
7. Use of the aminated and gold nanoparticle-loaded polydopamine film-vertically ordered mesoporous silica film composite film modified electrode according to claim 6 in detecting acetaminophen.
Citation Information
Patent Citations
Preparation method of electrochemical sensor with surface curing polypeptide probe
CN106290520A
Gold-nanoparticle-contained mesoporous composite film electrode and preparation method and application thereof.
CN110196271A